Penerapan Model Pembelajaran Jerrold E KEM Di SMP Hanuru - Novita Loma Sahertian; David Ming; Hestyn Natal Istinatun; Junio Richson Sirait (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
This study intends to apply a learning model including: development of a syllabus and a Learning Implementation Plan (RPP) cooperative type time token type in PAK and Character In Class VIII, the material of Allah loves the world. The method used in this research was the descriptive qualitative research method. Data were collected through observation, interview, and literature study and analyzed in-depth and described descriptively. The action hypothesis is a temporary answer in the form of action on the formulation of the problems set out in this classroom action research which is: student learning outcomes will increase